PESAN MORAL DALAM KISAH UMAR BIN KHATTAB PADA KITAB AROBIYYAH LIN NASYII'N 4 - Abid Nurhuda (Yayasan Hurriah, Banda Aceh, 2021)
Abstract: The era of globalization is the era of humans who cannot be separated from communication because they are social beings whose nature wants to coexist. This usually has a specific purpose and can be done directly or indirectly, through the masses or non-mass. Non-mass communication is a very effective tool in conveying social messages or moral messages to readers. One of them in printed form is the book